A Critique of Concepts of Workable Competition - Sosnick, Stephen H. (Quarterly Journal of Economics, 1958)
Introduction, 380. — I. The nature of the theory of workable competition, 383. — II. The several concepts of workability, 386. — III. Performance norms and value judgments, 391. — IV. Necessary vs. sufficient conditions, 395. — V. Remediability vs. categorical norms, 402. — VI. The workability criterion reformulated, 410. — Appendix, 415.